Numerical investigation of composite materials thermo-mechanical behaviour during ultrasonic welding in different mediums. (2023) - Prakash, Anand; Bose, Sandeep; Ponappa, K.; Chelladurai, H.
Abstract: Ultrasonic welding (USW) creates highly efficient solid-state weld for composite with low power consumption. At the joint contact, a unique diffusion layer is formed during the process, which experiences significant plastic deformation at glass transition temperatures. As the use of composite increases in marine, oil, and gas transport applications, ultrasonic welding becomes the most popular welding process for weld composites. In the marine application, there is a need to weld the part underwater, underwater welding by other conventional welding methods is too much difficult due to the high temperature generated by the welding torch. This temperature can easily break the hydrogen and oxygen bond, and this could cause an explosion underwater. This phenomenon is the same for the oil and gas transportation industry. So, to minimize the risk ultrasonic welding is the most significant welding process. This paper presents the numerical simulation of ultrasonic welding of composites in a different medium. The numerical model may provide an understanding of the thermal phenomena influencing the joining process, as well as an estimation of the impact. The simulation findings revealed that the clamping pressure, vibration frequency, and friction coefficient all have a significant impact on heat and stress produced during the process, which is crucial in determining the ultimate quality of the welded joint. The maximum temperature developed during numerical investigation of USW in the air is 80.51 °C and in water is 72.67 °C and the maximum stress developed during USW in the air is 13.22 MPa and in water is 10.21 MPa these conditions are sufficient for welding composites. According to studies, higher clamping force and welding frequency also resulted in increased distortion.